Composition and distribution of Gammarid Amphipods in a NaGISA rockyshore site, Taklong Island National Marine Reserve (2012). - Doce, Sydney D.
A NaGISA Rocky shore site in Taklong Island National Marine Reserve was the study site for the assessment of gammarid composition and distribution as well as their relationship with the different tidal levels. Sampling was done following the NaGISA protocol on October 18, 2012 with 27-meter transect lines laid on the THT (high tide), TMT (mid tide), TLT (low tide), and TST (13 depth, subtidal) parallel to the shore. The overall mean Gammaridean density was 187 ind?m-2 composed of organisms belonging to 6 families dominated by Corophiidae (51%) and Gammaridae and Isaeidae (13%). The other families are Ampithoidae and Photidae (3%) and Ischyoceridae. Gammaridean densities and their species diversity and evenness indices showed a fluctuating trend with respect to tides while dominance showed an increasing trend, implying that there is dominance mainly in the subtidal. One-Way ANOVA showed that densities were not significantly different (F=2.796, p= 0.07) among tidal levels, as well as within the transects (F=0.36, p= 0.78). Macroalgal biomass showed a strong positive correlation (R=0.889) with the mean Gammaridean densities since macroalgae can serve as habitat for this organisms, can be a source of detritus as well as shelter to protect them from abrupt changes in the intertidal. Only two families were present in the high tide zone (THT) because parts of this region are exposed to the air for long periods as the tide recedes. The mid tide zone (TMT) houses two families since it is covered and uncovered by tides on a shorter, more regular cycle. The low tide zone (TLT) has all the six families present and is the most diverse among the tidal levels however, the densities of gammarids is low. The low stability of this zone is attributed to the fluctuating water levels and destructive wave action. Overall, the Subtidal (TST) is the most preferred habitat of the gammarids because of its environmental stability being rich in organic matter content and it is always submerged in water.